2004
DOI: 10.1021/ja047169n
|View full text |Cite
|
Sign up to set email alerts
|

Digital Photoswitching of Fluorescence Based on the Photochromism of Diarylethene Derivatives at a Single-Molecule Level

Abstract: Photochromic reactions of diarylethene derivatives were detected at a single-molecule level by using a fluorescence technique. Fluorescent photoswitching molecules in which photochromic diarylethene and fluorescent bis(phenylethynyl)anthracene units are linked through an adamantyl spacer were synthesized, and switching of fluorescence upon irradiation with UV and visible light was followed in solution as well as on polymer films at the single-molecule level. Although in solution the fluorescence intensity grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
228
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(235 citation statements)
references
References 65 publications
4
228
0
3
Order By: Relevance
“…9). The results are encouraging and competent in the application environments requiring super switching speed and high-fluorescence on/off switching ratio [26][27][28] . In addition, the photodynamic processes of PMI-nDTEs monitored by absorption and fluorescence spectra have been investigated in dilute toluene solution.…”
Section: Resultsmentioning
confidence: 82%
“…9). The results are encouraging and competent in the application environments requiring super switching speed and high-fluorescence on/off switching ratio [26][27][28] . In addition, the photodynamic processes of PMI-nDTEs monitored by absorption and fluorescence spectra have been investigated in dilute toluene solution.…”
Section: Resultsmentioning
confidence: 82%
“…The first published observation of what is known today as photochromism dates back to 1867, when Fritzsche found that an orange-coloured solution of tetracene tends to bleach in the day light, regenerating its color in the dark [4]. During the past decades, researching into photochromism has received a powerful impulse, more and more achievements on synthesis and studying its properties in the new families of organic photochromic molecules have been published [5][6][7], because of their widespread potential application in photonic devices [8,9]. Among the photochromic compounds, diarylethene derivatives are the most promising candidates for potential application to optical memory media and optical switches for their thermal stability and fatigue resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The fast and reliable reversible photoswitching of Dronpa at the singlemolecule level is in contrast with other GFP mutants (11) and diarylethene derivatives (6,7). This achievement could be explained by the fact that switching requires only minimal structural changes of the chromophore (protonation͞deprotona-tion instead of ring closure reactions).…”
Section: Single-molecule Fluorescence Spectroscopy Uncovers the Photomentioning
confidence: 96%
“…A photoswitch exhibits two stable and selectively addressable states, a fluorescent and a nonfluorescent, which can be conveyed into another in a reversible fashion upon irradiation with different wavelengths of light. Although highly reproducible optical switching of individual chromophores could be achieved in liquid helium temperature experiments (5), the synthetic approach based on a photoswitchable diarylethene derivative was crowned with success only recently (6,7). Very recently (8,9), it was demonstrated that even conventional unmodified carbocyanine derivatives such as Cy5 can function as efficient reversible single-molecule photoswitches.…”
mentioning
confidence: 99%